Understanding the Effects of Emergency Experience on Online First-Aid Learning Intention: The Mediating Role of Psychological Distances and Prosociality - Zhang, Shuo; Guo, Huijing; Ju, Xiaofeng; Ma, Jiantao (Frontiers in Psychology, 2022)
The fast-paced lifestyle resulting from China’s rapid economic development has caused more than 500 million sudden cardiac deaths in 2020. Online first-aid education for the public is considered a key potential solution to avoid such incidents and would have great practical value. This study focuses on understanding the impact of past first-aid experience on the intention for online learning of first-aid knowledge and skills from the perspective of individual psychological factors based on the construction level and prosociality theories. More specifically, it tests the mediating roles of psychological distances and prosociality, which reflect psychological status, in the relationship between experience and learning intention along with a series of associated demographic variables. Primary data collected via a survey are analyzed through regression analysis. The results show that first-aid experience has a significant positive impact on online first-aid learning intention. In addition, psychological distances from first-aid events, and prosociality, play mediating roles in the relationship between first-aid experience and learning intention. Thus, this study contributes to understanding first-aid learning intention by revealing the impact of the individual factors of psychological distances and prosociality.